Determination of serum inflammatory markers in response to a plant-based protein dietary intervention - Mikkola, Laura (My University, 2025)
Diet has a considerable impact on inflammation, as it can either increase or reduce it, depending on environmental factors. Interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) are inflammatory markers connected to the maintenance of homeostasis within the body. High sensitivity C-reactive protein (hs-CRP) is a marker of low-grade inflammation used to identify inflammatory processes. The aim was to examine whether short-term consumption of plant-based protein foods with three different processing levels have notable effects on inflammatory markers. A total of 37 healthy adult volunteers in the age range of 18-65 and in the BMI range of 18.5-27 participated in a randomized cross-over intervention study. Quantitative assessment of serum IL-6 and TNF-α was performed with enzyme linked immunosorbent assay (ELISA). The results were later compared with hs-CRP concentrations analyzed in TYKSlab. This study was done as a part of the Newplant research project. Different processing levels did not significantly affect marker concentrations. The second most processed diet (diet 2) resulted in a significant outcome on TNF-α, and hs-CRP compared to baseline concentrations. During diet 2, the concentrations of TNF-α increased on average by 25 %, while hs-CRP decreased by 34 %. Correlation tests between diets and inflammatory markers showed a moderately strong positive correlation between IL-6 and hs-CRP on diet 2, and between IL-6 and TNF-α on the most processed diet (diet 3). Products from diet 3 were consumed the most according to the instructions by research group (47.1 %), followed by diet 2 (44.4 %) and diet 1 (32.4 %). Contrary to the hypothesis, diet 3 was the only one showing a decreasing effect. However, comparing median concentrations of inflammatory markers’ pre- to post intervention, all diets showed a decreasing effect.
Keywords: Dietary intervention, ELISA, food processing, inflammatory markers, low-grade inflammation, plant-based products, plant proteins